PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI SETDA KABUPATEN BULELENG - Ni Luh Putu Eka Pradnyawati; Ni Luh Wayan Sayang Telagawathi; Nana Trianasari (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This aim of the research was conducted to determine the role of job satisfaction as a mediating influence of organizational culture and organizational commitment on the performance of employees of the Regional Secretariat of Buleleng Regency. The research design used is causal quantitative. The objects of this research are organizational culture, organizational commitment, job satisfaction, and employee performance. The subjects of this study were ASN employees in the Regional Secretariat of Buleleng Regency. The population used in this research is all ASN employees in the Regional Secretariat of Buleleng Regency. Collecting data through questionnaires and observation. Researchers use SEM PLS for data analysis techniques. The results of this study state that: (1) Organizational culture has a positive and significant influence on employee performance in the Regional Secretariat of Buleleng Regency. (2) Organizational commitment has a positive and significant influence on employee performance in the Regional Secretariat of Buleleng Regency. (3) Organizational culture has a positive and significant influence on job satisfaction in the Regional Secretariat of Buleleng Regency. (4) Organizational commitment has a positive and significant effect on job satisfaction in SETDA Buleleng Regency. (5) Job satisfaction has a positive and significant effect on employee performance in the Regional Secretariat of Buleleng Regency. (6) The role of job satisfaction as a mediation has a positive and significant effect on the influence of organizational culture on employee performance in the Regional Secretariat of Buleleng Regency. (7) The role of job satisfaction as a mediation has a positive and significant effect in mediating the effect of organizational commitment on employee performance in the Regional Secretariat of Buleleng Regency.